Combined individual scrummaging kinetics and muscular power predict competitive team scrum success - Green, A.; Dafkin, C.; Kerr, S.; McKinon, W. (European Journal of Sport Science, 2017)
Scrummaging is a major component of Rugby Union gameplay. Successful scrummaging is dependent on the coordination of the forward players and the strength of the eight individuals. The study aim was to determine whether individual scrummaging kinetics and other candidate factors associated with scrummaging performance discriminate team scrum performances. Sixteen club-level forwards (stature: 1.80 ± 0.1 m; mass: 99.0 ± 18.2 kg) were initially divided into two scrummaging packs. A total of 10 various scrum permutations were tested, where players were randomly swapped between the two packs. Winning scrums were determined by two observers on opposite sides of the scrum. Fatigue (100 mm visual analogue scale (VAS)) and scrummaging effort (6-20 rating of perceived exertion (RPE)) were assessed following each scrum contest. Individual scrummaging kinetics were acquired through an instrumented scrum ergometer and muscular power indicated through vertical jump heights. Student`s t-tests were used to differentiate between winning and losing scrum packs. VAS and RPE were assessed using repeated measures ANOVAs. Winning scrum packs had significantly larger combined force magnitudes (p < .002), regardless of the player contribution calculations. Additionally, winning packs had less individual movement (p = .033) and higher combined vertical jump heights (p < .001) but were not significantly heavier (p = .759) than losing scrum packs. While perceived VAS and RPE values progressively increased (p < .001), no differences in the individual scrum magnitudes were observed between the 1st and 10th scrum (p = .418). The results indicated that the combination of individual forces, variation in movement and factors related to scrummaging performance, such as vertical jump height, were associated with team scrummaging success.